Price Effects on Compound Commodities - Junichi Minagawa; Thorsten Upmann (Center for Economic Studies and ifo Institute (CESifo), 2016)
We explore effects of simultaneous price changes for the demand of a group of goods, which we refer to as a compound commodity. Specifically, we consider unit and proportional cost components (e. g., taxes, transportation costs, etc.) imposed on the compound commodity. We find that there is a serious aggregation problem implying that the property of a downward-sloping demand curve does not generally hold for the demand of a compound commodity. Notably, both substitution effects of the unit cost and of the proportional cost for a compound commodity may be unambiguously opposed. Finally, we apply these results to commodity taxation.
Keywords: D01; D11; H20; 330; demand for a group of goods; compound commodity; unit and proportional costs; income and substitution effects; Slutsky equation; Giffen goods